"Il Corpo Ritrovato": Dermocosmetological Skin Care Project for the Oncologic Patient. (13th April 2011) - Fabbrocini, G.; Romano, M. C.; Cameli, N.; Mariano, M.; Pastore, F.; Annunziata, M. C.; Mazzella, C.; De Vita, Valerio; Mauriello, Maria Chiara; Monfrecola, G.
Abstract : Neoplastic disease and its therapeutic options have a huge impact on the patient's quality of life from both the emotional and the working point of view. The project "Il Corpo Ritrovato" aims at creating an interdisciplinary network of physicians to improve the quality of life of the oncologic patient, focusing on such important aspects as dermocosmetological skin care but also on the evaluation of new therapeutic and diagnostic algorithms in order to make further progress in the field of prevention.